Gemingde youyi (Yazhou, Feizhou, Lading Meizhou pengyoumen canguan Zhongguo renmin geming junshi bowuguan) - Shen Jialin,
'Revolutionary friendship (Friends from Asia, Africa and Latin America visit the Museum of the Chinese revolutionary army)'. Print no. 8085.2589.